2014
DOI: 10.1016/j.coph.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Brain peptides and the modulation of postoperative gastric ileus

Abstract: Postoperative ileus (POI) develops after abdominal surgery irrespective of the site of surgery. When prolonged, POI can lead to longer hospitalization times and higher healthcare costs. Moreover, it is associated with complaints for the patient. In order to develop new strategies to treat this condition, a deeper understanding of the pathophysiology of the POI is necessary. This review will focus on brain peptides (ghrelin, nesfatin-1, somatostatin, corticotropin-releasing factor, thyrotropin-releasing hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…The casual relationship between inflammation and motility disorder in POI needs to be clarified. It was previously reported that the accumulation of pro-inflammatory cytokines and increased expression of NO could be reduced by hesperidin through inhibition of NO related pathways, which was also confirmed in our study [3][4][5][6] . We believe that hesperidin exerts anti-inflammatory effects on POI, ameliorating the digestive motor inactivity in POI rats and accelerating gastrointestinal transit.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The casual relationship between inflammation and motility disorder in POI needs to be clarified. It was previously reported that the accumulation of pro-inflammatory cytokines and increased expression of NO could be reduced by hesperidin through inhibition of NO related pathways, which was also confirmed in our study [3][4][5][6] . We believe that hesperidin exerts anti-inflammatory effects on POI, ameliorating the digestive motor inactivity in POI rats and accelerating gastrointestinal transit.…”
Section: Discussionsupporting
confidence: 90%
“…As one of the postoperative dysmotility disorders of the gastrointestinal tract, postoperative ileus remains one of the most perplexing problems in medicine [3,4] . Because prolonged POI is an iatrogenic condition leading to prolonged hospitalization resulting in increased health care costs, the development of effective management strategies to prevent POI is clinically important [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGRP signaling has also been implicated as a mediator of the postoperative gastric ileus and inflammation that often occurs with abdominal surgery. Preclinical studies in dogs, rats, and mice have shown that the peptide CGRP receptor antagonist CGRP 8‐37 , the CGRP‐RA olcegepant, and an anti‐CGRP antibody improve postoperative gastric emptying …”
Section: Comparing the Cgrp Antibodies Clinicallymentioning
confidence: 99%
“…Pharmacological activation of brain sst 2 also prevents visceral stress-related inhibition of food intake, e.g. during postoperative gastric ileus known to involve CRF (Stengel and Taché, 2014b) adding to existing evidence that brain somatostatin counteracts several functional responses to acute stressors by interacting with CRF (Stengel et al, 2013). …”
Section: Discussionmentioning
confidence: 99%